Understanding Communalism In India's Multicultural Fabric: A Comprehensive Exploration - U Din Mir., Mehraj (International Journal of Psychosocial Rehabilitation, 2024)
An overview of the thorough investigation into the phenomena of communalism within the varied setting of India is given in this abstract. India, a country known for its vibrant multiculturalism, has seen significant communal dynamics in its social and political environment. This research explores the complex interactions between communalism and the varied religious, cultural, and ethnic fabric of the nation. It attempts to explain the antecedents, underlying factors, and present-day manifestations of racial tensions using a comprehensive approach. This investigation tries to clarify the intricacies surrounding communalism by looking at significant events, sociopolitical variables, and the function of media and education. It also examines the threats communalism poses to India's secular ethos as well as the initiatives made to promote social cohesion and interfaith peace. This study offers insights into how communalism affects India's multicultural identity through the use of an objective lens, and it suggests potential solutions for dealing with this problem in order to create a more peaceful and inclusive society.